The immigrant left in the United States - Buhle, Paul, 1944-; Georgakas, Dan (SUNY series in American labor history., 1996)
This book investigates the role immigrant radicals have played in U.S. society from the mid-nineteenth century to the present. A valuable contribution to the history of the American Left, it makes use of a wealth of material from immigrants whose everyday speech and intellectual discourse were not in the English language. The social-history scholarship that informs the essays is innovative in method and purpose. Articles on Mexican-American, German, Jewish, Polish, Japanese, Chinese, Filipino, Italian, Ukrainian, Greek, Arab, and Haitian immigrants supply missing conceptual links between the immigration experience, the neighborhood and the workplace, and political, labor, and cultural institutions. Taken together, they offer a model study in transnational history, one the most important new fields of historical inquiry.